Pengaruh Opini Audit, Temuan Audit, dan Tindak Lanjut Hasil Pemeriksaan Terhadap Kualitas Pengungkapan Laporan Keuangan Kementerian/Lembaga - Muhammad Daffa Pramasta; Widyasari Widyasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines the effects of audit opinions, audit findings, and follow-up on quality of financial statements disclosures within government ministries/agencies. The disclosure quality of these financial statements is measured by comparing the number of items actually disclosed in the Notes to Financial Statement against the total mandatory disclosures required under Statement of Governmental Accounting Standards 04. Utilizing a purposive sampling method, data were gathered from the official website of the Audit Board of the Republic of Indonesia. The final observation dataset comprised 228 samples of audited financial statements from ministries/agencies spanning the fiscal years 2021 to 2023. Employing panel data regression analysis, this study demonstrates that audit opinions have no significant effect on disclosure quality. Conversely, audit findings exert a significant negative impact on disclosure quality, whereas the audit follow-up has a significant positive influence. These findings substantiate agency theory, illustrating that identified audit findings and the subsequent follow-up serve as strong signaling mechanisms for external oversight in assessing the financial statement disclosure quality of government institutions.